Combining Deconvolution and Noise Analysis for the Estimation of Transmitter Release Rates at the Calyx of Held - Neher, Erwin (J Neurosci, 2001)
The deconvolution method has been used in the past to estimate release rates of synaptic vesicles, but it cannot be applied to synapses where nonlinear interactions of quanta occur. We have extended this method to take into account a nonlinear current component resulting from the delayed clearance of glutamate from the synaptic cleft. We applied it to the calyx of Held and verified the important assumption of constant miniature EPSC (mEPSC) size by combining deconvolution with a variant of nonstationary fluctuation analysis. We found that amplitudes of mEPSCs decreased strongly after extended synaptic activity. Cyclothiazide (CTZ), an inhibitor of glutamate receptor desensitization, eliminated this reduction, suggesting that postsynaptic receptor desensitization occurs during strong synaptic activity at the calyx of Held. Constant mEPSC sizes could be obtained in the presence of CTZ and kynurenic acid (Kyn), a low-affinity blocker of AMPA-receptor channels. CTZ and Kyn prevented postsynaptic receptor desensitization and saturation and also minimized voltage-clamp errors. Therefore, we conclude that in the presence of these drugs, release rates at the calyx of Held can be reliably estimated over a wide range of conditions. Moreover, the method presented should provide a convenient way to study the kinetics of transmitter release at other synapses.